2021
DOI: 10.1093/hmg/ddab229
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-wide association study identifies novel blood-based gene biomarker candidates for Alzheimer’s disease risk

Abstract: Alzheimer’s disease (ad) adversely affects the health, quality of life and independence of patients. There is a critical need to identify novel blood gene biomarkers for ad risk assessment. We performed a transcriptome-wide association study to identify biomarker candidates for ad risk. We leveraged two sets of gene expression prediction models of blood developed using different reference panels and modelling strategies. By applying the prediction models to a meta-GWAS including 71 880 (proxy) cases and 383 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…17 Notably, we modified the original script of UTMOST by using uniform hyperparameters across different folds to make the hyperparameters directly comparable. 17,25 We confirmed that the modified UTMOST gave an unbiased estimate of prediction performance using empirical datasets. 21 Details of the modification can be found at https://github.…”
Section: Building Normal Prostate Tissue Gene Expression Prediction M...supporting
confidence: 64%
“…17 Notably, we modified the original script of UTMOST by using uniform hyperparameters across different folds to make the hyperparameters directly comparable. 17,25 We confirmed that the modified UTMOST gave an unbiased estimate of prediction performance using empirical datasets. 21 Details of the modification can be found at https://github.…”
Section: Building Normal Prostate Tissue Gene Expression Prediction M...supporting
confidence: 64%
“… Novikova et al (2021) integrated AD GWAS data with myeloid-specific epigenomic and transcriptomic datasets, and identified 11 genes as risk factors for AD to 20 loci. Sun Y. F. et al (2022) utilized two gene expression prediction models of blood to predict meta-GWAS data, determining the expression of 108 genes in blood associated with AD risk, and identified 15 differentially expressed genes (DEGs). Kosoy et al (2022) employed transcriptional and chromatin accessibility analysis on primary human astrocytes derived from 150 donors to identify putative regulatory mechanisms of 21 AD risk loci.…”
Section: Methods Of Identification Of Candidate Biomarkers For Admentioning
confidence: 99%
“…Multi-omics analyses are well-established to discover functional genes, drug targets, and biomarkers in various complex diseases, including neurological disorders [22,[31][32][33][34], cancers [35][36][37][38][39], and cardiovascular disease [40]. Multi-omics data integration provides an innovative avenue to bring multi-layer biological information to systematically identify novel insights into the complex pathobiology of diseases [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…TWAS framework integrates eQTLs data with GWAS to reveal associations between genes and traits [13]. TWAS studies determine the association of genetically predicted gene expression levels of genes with complex traits; the TWAS framework is unable to provide the effect of causal strength of the variants and horizontal pleiotropy [22]. Colocalisation is also an integrative gene-prioritisation method that integrates eQTLs data with GWAS signals to identify the co-occurrence of variants between pairs of traits [23].…”
Section: Introductionmentioning
confidence: 99%